Pengaruh Pendidikan Kesehatan Reproduksi Menggunakan Metode Mentoring terhadap Pengetahuan Remaja Tentang Kesehatan Reproduksi: The Effect of Reproductive Health Education Using the Mentoring Method on Adolescents' Knowledge of Reproductive Health - Yanti Puspita Sari; Lora Desi Mulyanti; Tuti Oktriani (NERS Jurnal Keperawatan, 2015)
Based on the results of a survey conducted by the Ministry of Health, published in 2012 showed that the level adolescent understanding of reproductive health is still very low. The consequences of the lack of knowledge of adolescents to reproductive health is vulnerable adolescents experiencing problems related to sexual and reproductive health. This study aims to look at the effect of reproductive health education using mentoring method for knowledge of adolescent about reproductive health. Research conducted in SMPN4 Palembayang. This quantitative research using pre experiment with one group pretest-posttest design. The population in this study all students of SMPN4 Palembayang using multistage random sampling technique. The number of respondents who used a sample of 15 people. This study uses data analysis techniques Paired T Test. The result of thorough statistical test p=0.000(p <0.05). Based on the results obtained by the value of p, we conclude there is a significant relationship between reproductive health education using mentoring to adolescent reproductive health knowledge. Further research is necessary to develop a prototype models to find an adolescent reproductive health education with a better structured.